THE ROLE OF ARTIFICIAL INTELLIGENCE (AI) CHATBOTS IN DEVELOPING STUDENTS’ ENGLISH SPEAKING FLUENCY - Bekchanova Mahliyokhon Hamidjon kizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Artificial Intelligence (AI) has become one of the most influential technological innovations in modern education. The rapid development of digital technologies has changed traditional teaching methods and created new opportunities for interactive and personalized learning. In recent years, AI chatbots have gained significant popularity in language education because they help students improve communication skills through continuous practice and real-time interaction. In English language learning, speaking fluency is considered one of the most important skills, as it allows learners to communicate effectively in academic, professional, and social environments. However, many students experience difficulties in speaking English fluently because of limited vocabulary, pronunciation problems, fear of making mistakes, and lack of confidence. Traditional classroom methods often cannot provide enough speaking opportunities for every learner due to limited lesson time and large class sizes. Therefore, the integration of AI chatbots into language education has become an effective solution for improving students’ oral communication skills.